(untitled) (Journal of the College of Basic Education, 2022)
This research gives a medical picture about the meaning of the kidney, starting with defining the kidney as an important part of the human body, and knowing its functions represented in getting rid of the body from the remnants of nutritional transformations and toxic substances and controlling the water balance in the body, and clarifying the concept of kidney failure and the types and stages of kidney failure, its causes and complications , down to the treatment methods represented by hemodialysis through the artificial kidney, peritoneal filtration, and finally treatment through surgery and kidney transplantation from another donor as a treatment method that restores the individual to his physiological health and reintegration into society.